ESTIMATING THE IMPACT ON THE LEASING OF HOUSEHOLDS OF FARMERS IN THE RURAL AREA - Emil MUȘAT (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2015)
Leasing is the most common operation on the land market, at least in areas with a high quality agricultural land. The Romanian legislation in post-communist period leasing experienced a special regulation to introduce it in the new Civil Code, thus recognizing the importance it has in the socio-economic rent in Romania. From this perspective, the lease determining role in the Romanian society is a useful approach to determine regulatory requirements and how the current legislation covers the needs of society. Based on statistical data obtained from the National Institute of Statistics in conjunction with the data collected from the performance of contracts of lease rent in the areas where agricultural land is a very common operation (counties Calarasi, Ialomita, Giurgiu. An image was created on the living standard of the rural farming households and the conclusion drawn is that although the leasing company has only a strong economic role, down to the grassroots level in the households examined, the role of leasing also acquires social issues.